THE EFFECT OF PERCEPTIONS OF BENEFITS, RISK AND SERVICE FEATURES ON INTEREST IN USING SHOPEEPAY AMONG ACCOUNTING STUDENT - Agustina, Ruslinda; Saputra, Indra (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study is to empirically prove the effect of perceived benefits, risks, and service features on the interest in using ShopeePay (on students majoring in accounting at STIE Nasional Banjarmasin). The research method used in this research is a quantitative method with a survey method through distributing questionnaires to students majoring in accounting at STIE Nasional Banjarmasin with a sample of 100 students who are respondents assisted by statistical tools using SPSS version 22.00 for Windows. The results of this study indicate that the perceived benefit variable affects the interest in using ShopeePay with a significance value of 0.020, the risk variable affects the interest in using ShopeePay with a significance value of 0.006, the service feature variable affects the interest in using ShopeePay with a significance value of 0.00. The results of the study simultaneously affect the interest in using ShopeePay with a significance value of 0.000. In conclusion, partially and simultaneously perceptions of benefits, risks and service features affect the interest in using ShopeePay among students majoring in accounting at STIE Nasional Banjarmasin. Suggestions for further researchers can add other variables such as convenience and trust that affect the interest in using e-money, and can expand the research sample.